ChemInform Abstract: Trapping of Carbolithiation‐Derived Tertiary Benzylic α‐Lithio Piperidines with Carbon Electrophiles: Controlling the Formation of α‐Amino Quaternary and Vicinal Stereocenters. Issue 50 (December 2015) - Beng, Timothy K.; Fox, Nathan; Bassler, Daniel P.; Alwali, Amir; Sincavage, Kayla; Silaire, Ann Wens V.
Abstract: The carbolithiation of 2‐aryl N‐Boc‐piperidines (I) followed by quenching with MeOH gives rise to 3‐alkylated trans‐products with high diastereoselectivity.